Pengembangan Buku Cerita Bergambar Berbasis Pendidikan Karakter Dalam Menumbuhkan Budaya Literasi Siswa Kelas II SD - Palupi Mutiasih; Prana Dwija Iswara; Trisna Nugraha (Universitas Sarjanawiyata Tamansiswa, 2021)
This development research aimed to produce picture book products based on character education that can improve literacy culture in elementary schools. A picture story book is a book that combines text and illustrations so that it becomes a story book that can increase students' reading interest. Picture story books can tell a story that is collaborated with an interesting and meaningful concept for children's development. The method used was the method of research and development (R&D) with the development model of Borg and Gall. This research and development had 9 stages of research, namely research and information gathering, planning, product draft development, initial field testing, product revision, main field test, operational product revision, field implementation test and final product revision. Respondents in research and development involved one material expert, one linguist, one media expert, 13 students of SDSN Bendungan Hilir 12 Pagi, 21 students of SDS Ar-Rahman Motik. The results showed that the character education-based picture book product was considered very good. The average result according to the expert was 97.1%, the Small Group Evaluation was 96.6%, and the Field Test was 94.33%. This picture book product was attractive to students who loved reading because reading was the key to increase literacy culture since elementary school age.